2017
DOI: 10.1007/s11695-017-2840-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Goal-Directed Fluid Therapy via Pleth Variability Index During Laparoscopic Roux-en-Y Gastric Bypass Surgery in Morbidly Obese Patients

Abstract: There is no need to administer extra volume of fluid to obese patients undergoing laparoscopic bariatric surgery. Use of dynamic indicators like PVI helps to decrease intraoperative volume of infused fluids with no effects on either intraoperative or postoperative lactate levels in laparoscopic bariatric interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Several studies have shown that PVI guided GDFT, when compared to fluid therapy guided by static parameters of fluid responsiveness, can lead to decreased infused fluid volume, decreased time to first stool, and decreased perioperative lactate levels [12, 13, 23, 24]. Trials comparing different GDFT strategies to PVI, such as esophageal Doppler, have however resulted in conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PVI guided GDFT, when compared to fluid therapy guided by static parameters of fluid responsiveness, can lead to decreased infused fluid volume, decreased time to first stool, and decreased perioperative lactate levels [12, 13, 23, 24]. Trials comparing different GDFT strategies to PVI, such as esophageal Doppler, have however resulted in conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding is a rare but serious complication, occurring in < 1% of patients, and can be prevented with a standard intraoperative protocol that increases blood pressure and reduces the pneumoperitoneum to identify possible silent bleeding sites . Goal‐directed fluid therapy is also recommended during bariatric surgery, and the potential for excessive IV fluid administration can be mitigated using dynamic indicators, such as the Pleth Variability Index (PVI) .…”
Section: Executive Summarymentioning
confidence: 99%
“…Intraoperative and postoperative fluid management in patients undergoing bariatric surgery should be goal directed . Utilizing continuous noninvasive measurements of fluid status, such as the PVI, stroke volume variation, or other technologies, results in less fluid administration during bariatric surgery than empiric calculations of volume requirements or by monitoring urine output . Administration of excess IV fluids can increase the rate of postoperative nausea and length of stay after surgery .…”
Section: Executive Summarymentioning
confidence: 99%
“…Proper fluid balance is therefore suggested. Goal‐directed fluid therapy may be useful to optimize intraoperative fluid management. Compared with a conservative/restrictive approach, liberal intraoperative fluid management during bariatric surgery does not reduce the incidence of rhabdomyolysis nor increase intraoperative urine output.…”
Section: Resultsmentioning
confidence: 99%